Manajemen BK Komprehensif: (Studi layanan Bimbingan dan Konseling di SMA Negeri 1 Cisarua Bandung Barat) (Jurnal Bimbingan dan Konseling Islam, 2019)
This research aims to describe the comprehensive guidance and counseling service program at SMAN1 Cisarua. This research is a descriptive qualitative research. Data collection techniques used were interviews, documentation, observation and data checklist. Data were analyzed descriptively qualitatively with the data triangulation model. Overall the stages carried out in the guidance and counseling service at SMAN 1 Cisarua, all aspects have fulfilled the Comprehensive BK component. The guidance and counseling program is described in four main activities, namely: 1) basic guidance services, 2) responsive services, 3) individual planning services, 4) system support